2005
DOI: 10.1001/archinte.165.2.234
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Medication Symptoms in Primary Care

Abstract: Primary care physicians may be able to reduce the duration and/or the severity of many ADEs by eliciting and addressing patients' medication symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
101
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 22 publications
5
101
2
Order By: Relevance
“…[19] Given that 36% of our respondents cited a health professional as a method of identifying a suspected ADR, it is unsurprising that 57% of all those who had this experience claimed they had discussed their experience. Previous work has shown that in response to reporting of symptoms suspected by patients to be ADRs, the most common action of primary care physicians was to discontinue the offending medicine or to change therapy, [4] as was found here. However other work has suggested that physicians may sometimes be dismissive [11,12] and we also found a small number of patients who experienced this type of response.…”
Section: Comparison To the Literaturesupporting
confidence: 59%
See 2 more Smart Citations
“…[19] Given that 36% of our respondents cited a health professional as a method of identifying a suspected ADR, it is unsurprising that 57% of all those who had this experience claimed they had discussed their experience. Previous work has shown that in response to reporting of symptoms suspected by patients to be ADRs, the most common action of primary care physicians was to discontinue the offending medicine or to change therapy, [4] as was found here. However other work has suggested that physicians may sometimes be dismissive [11,12] and we also found a small number of patients who experienced this type of response.…”
Section: Comparison To the Literaturesupporting
confidence: 59%
“…Two large prospective studies in Liverpool hospitals have shown that 6.5% out of 18,820 admissions to medical units were caused by adverse drug reactions (ADRs), that 2.3% of patients admitted with ADRs die [1] and that 14.7% of 3,695 medical or surgical in-patients experienced an ADR during their stay. [2] In primary care, studies which have relied on patients' reports of ADRs, either to postal questionnaires or telephone surveys suggest annual prevalence estimates of the order of 25-29% in the USA [3,4] and 30% in the UK. [5] Higher estimates were found in a Dutch study involving only anti-epileptic drugs.…”
Section: Conclusion Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient self-reports of adverse drug events (ADEs) are an important additional source of information on the safety of drugs because they differ from healthcare professional reports [2][3][4][5][6][7]. Healthcare professionals often underestimate symptomatic ADEs experienced by patients [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Elderly patients may be unable to recognise the symptoms of conditions that increase the risk of falls, such as hypotension or dizziness; or they may not report them to their healthcare givers, increasing the risk of experiencing falls, if the medication regimen is not adjusted (248). Safety issues of medications with repeat prescribing, including antihypertensive medications, have also been warranted (249).…”
Section: Discussionmentioning
confidence: 99%